DIAGNOSTIC IMAGING IN CROHN'S DISEASE - G.M. ZHARGALOVA; P.V. SELIVERSTOV (Паёми Сино, 2025)
Crohn's disease (CD) is an inflammatory bowel disease with an unknown etiology, and many authors suggest that its prevalence is steadily increasing worldwide. Among the various diagnostic methods available, ileocolonoscopy with biopsy is considered the "gold standard" for detecting intestinal diseases. However, since CD can affect any part of the gastrointestinal tract, this method has limitations. It cannot examine the proximal parts of the small intestine or evaluate all layers of the intestinal wall. Furthermore, this invasive procedure is often poorly tolerated by patients, making it less applicable for repeated use. Non-invasive imaging techniques, such as ultrasound examination (US), computed tomography enterography (CT enterography), and magnetic resonance enterography (MR enterography), have proven effective in diagnosing CD. These methods can visualize not only the large intestine but also the small intestine, assess damage to the deeper layers of the bowel, and identify associated complications such as strictures, abscesses, and fistulas. Additionally, CT and MR enterography enable the assessment of other organs and systems within the scanned area, allowing for the identification of both CD-related and unrelated pathological conditions. Various CD activity indices have been proposed, most of which rely on MR enterography. However, none of these indices have achieved universal acceptance or are included in standard diagnostic protocols for CD. The search for information was conducted in databases such as PubMed, Medline, Scopus, eLibrary, and Cyberleninka, using keywords including "Crohn's disease", "ultrasound examination of the intestine", "CT enterography", and "MR enterography". Two types ofsearch queries were performed in the PubMed and Medline databases: a) using MeSH library terms like "Crohn's Disease/diagnosis" and "Crohn's Disease/diagnostic imaging", and b) using keywords like "ultrasound examination of the intestine", "CT enterography", and "MR enterography". This review analyzed 34 sources, of which 25 contained relevant data from the last ten-year period (2014-2024). The inclusion criteria for the review consisted of reviews, systematic reviews, randomized controlled trials, and meta-analysesthat focused on imaging studies of the intestine in patients with CD. Exclusion criteria included articles that discussed non-radiological-assisted methods for CD, studies involving patients with ulcerative colitis, and studies lacking full-text access.